1984
DOI: 10.3109/03009748409102666
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in the Serial Assessment of Disease Activity in Rheumatoid Arthritis

Abstract: C-reactive protein (CRP) levels were measured in 105 patients with rheumatoid arthritis (RA) during treatment with slow-acting anti-rheumatoid drugs D-penicillamine, alclofenac, hydroxychloroquine, gold, sulphasalazine and azathioprine. A control group treated with aspirin alone was also included. Patients were assessed clinically (pain score, articular index and summated change score) and in terms of acute-phase reactants (CRP, haptoglobin, fibrinogen, ESR and plasma viscosity) at eight separate clinic visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 12 publications
0
31
1
1
Order By: Relevance
“…CRP concentration is known to be elevated in human RA and has been used as an index of disease activity and a prognostic factor [7,9,19]. In the present study, the CRP concentrations at the time of diagnosis were markedly elevated in all the IPA dogs, but these could not predict the long-term outcomes of the disease/medication status.…”
Section: Discussionmentioning
confidence: 51%
“…CRP concentration is known to be elevated in human RA and has been used as an index of disease activity and a prognostic factor [7,9,19]. In the present study, the CRP concentrations at the time of diagnosis were markedly elevated in all the IPA dogs, but these could not predict the long-term outcomes of the disease/medication status.…”
Section: Discussionmentioning
confidence: 51%
“…Numerous studies have demonstrated the inability of NSAID therapy to influence serologic correlates of inflammation, including the ESR and CRP (2)(3)(4)(5)(6). Elevations in the levels of acute-phase reactants are characteristic findings in patients with active RA (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that changes in the concentration of CRP can reflect remission or exacerbation of RA [3]. Reductions in serum CRP have been shown to correlate with an improvement in clinical symptoms [4,5] and a decrease in radiologically assessed disease progression [6] measured via development of radiographic erosions [6,7].…”
Section: Introductionmentioning
confidence: 99%